The Sea Resource in the Mobility of Goods and People in the Campania Region - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2009)
The 512 kilometers of Campanian coastline represent a share of 6.7% in the whole Italian coastline (7,687 Km). The urban coastal system is a consolidated system; in it the structure of great and little cities and the harbour infrastructures are historically present: it is arguable that in course of time the system of port functions and the relative importance between them has changed, but it isn’t changed the number and the location. The Campanian coastal morphology has made possible the presence of port facilities of significant size. The harbour system is almost entirely developed in the central stretch of the coastal bell and is based on the ports of Naples and Salerno (freight and passengers), Torre Annunziata (freight), Castellammare di Stabia (shipbuilding), Pozzuoli (freight and passengers), and the system of ports, mainly with passenger traffic, of Ischia, Casamicciola, Capri, Procida, and Sorrento. This complex port system has many strengths and many weak-nesses, but it can give significant results to the asphyxial regional economy, in a perspective of territorial development; in fact some of the planning processes affecting the Region are focusing on possible actions to restore strength to the secular relationship between land and sea, accounted as one of the strong point of relevance in the Campania. The importance of a productive use of the maritime resources derives from two considerations: the first is the geographic position of Italy (and inside, Campania) in the Mediterranean and along the routes between Europe and Asia; the second is the impact of the transport of goods and passengers on the territorial and economic Campanian system. Analysis and findings change for the freight or passenger traffic; in the first case become significant the infrastructural capacities, the local production system, and their connections with other production systems outside the Region. In the second case is relevant the enhancement of cultural and environmental system areas and the quality of the tourist and travelers reception. The paper analyzes the state of the regional port system with the aim of defining an overall picture of the situation and the development processes. In particular it analyzes the role of the regional ports in the local, national and international freight and with a particular attention to the role of local production systems and logistic systems. Another element analyzed is the role of ports in the passenger traffic (local and cruise ship) and the evolutionary hypotheses in the planning process.